Digital Three-Dimensional Automation of the Modified Huddart and Bodenham Scoring System for Patients with Cleft Lip and Palate. (July 2017) - Ma, Xinhui; Martin, Catherine; McIntyre, Grant; Lin, Ping; Mossey, Peter
Objective: The modified Huddart and Bodenham scoring system assesses maxillary arch constriction and surgical outcomes in cleft lip and palate. This project automates modified Huddart and Bodenham scoring using three-dimensional digital models. Design: Development of a novel software tool. Setting: The design, construction, development, and testing of the system was carried out at Dundee Dental Hospital. Patients, Participants: Subjects with cleft lip and palate. Interventions: A plug-in has been developed using an open three-dimensional development platform: Rhinoceros, version 5 (http://www.rhino3d.co.uk ). Users select cusps on mandibular and maxillary teeth on three-dimensional digital models. A three-dimensional cubic spline generates a mandibular curve, and a best-fit horizontal mandibular reference plane is produced using a least-squares method. Horizontal distances projected from the shortest three-dimensional distances were subsequently calculated between the maxillary cusps and the mandibular curve to calculate the modified Huddart and Bodenham score. Main Outcome Measures: Automatic scoring of digital models using the modified Huddart and Bodenham system produces similar results to manual scoring. Results: By standardizing outcome assessment in cleft care, multicenter comparisons for audit and research can be simplified, allowing centers throughout the world to upload three-dimensional digital models or intraoral scans of the dental arches for remote scoring. Thereafter, these data can feed back into the global database on orofacial clefting as part of the World Health Organization's international collaborative "Global Burden of Disease" research project for craniofacial anomalies. Conclusions: The automated system facilitates quicker and more reliable outcome assessments by minimizing human errors.